Networks, Innovation and Public Policy - Considine, M. author. aut Link
XVI, 231 p. 25 illus.
Keywords: This book examines the different normative approaches politicians, bureaucrats and community actors use to frame the innovation puzzle, arguing that these create specific cultures of innovation. The authors explore the role of formal institutions and informal networks in promoting and impeding governmental innovation.